2019
DOI: 10.1111/tra.12637
|View full text |Cite
|
Sign up to set email alerts
|

Sfp1 links TORC1 and cell growth regulation to the yeast SAGA‐complex component Tra1 in response to polyQ proteotoxicity

Abstract: Chromatin remodeling regulates gene expression in response to the accumulation of misfolded polyQ proteins associated with Huntington's disease (HD). Tra1 is an essential component of both the SAGA/SLIK and NuA4 transcription co‐activator complexes and is linked to multiple cellular processes, including protein trafficking and signaling pathways associated with misfolded protein stress. Cells with compromised Tra1 activity display phenotypes distinct from deletions encoding components of the SAGA and NuA4 comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 135 publications
(345 reference statements)
2
6
0
Order By: Relevance
“…We previously found that Tra1 regulates the expression of genes associated with several stress responses including cell wall stress and the response to misfolded proteins ( Berg et al 2018 ; Jiang et al 2019 ; Razzaq et al 2021 ). Based on findings that tra1 Q3 cells have a shorter lifespan, we next sought to determine how the loss of Tra1 function impacts the transcriptional landscape of the aging cell.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that Tra1 regulates the expression of genes associated with several stress responses including cell wall stress and the response to misfolded proteins ( Berg et al 2018 ; Jiang et al 2019 ; Razzaq et al 2021 ). Based on findings that tra1 Q3 cells have a shorter lifespan, we next sought to determine how the loss of Tra1 function impacts the transcriptional landscape of the aging cell.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that Tra1 regulates the expression of genes associated with several stress responses including cell wall stress and the response to misfolded proteins (Berg et al . 2018; Jiang et al . 2019; Razzaq et al .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our analysis also shows significant enrichment in Sfp1 target genes and RLM1 targets ( FIGURE 1e ). Sfp1 interacts with Tra1 (68) and we recently demonstrated that Sfp1 regulates Tra1/SAGA-driven gene expression in response to protein misfolding (69). RLM1 controls gene expression of factors involved in the cell wall integrity pathway (CWI) (64), consistent with the tra1 Q3 causing increased sensitivity to cell wall perturbation (47).…”
Section: Resultsmentioning
confidence: 99%